Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) Terhadap Hasil Belajar Siswa Kelas X MIA pada Pokok Bahasan Larutan Elektrolit dan Non Elektrolit - Monica, Caroline; Hadinugrahaningsih, Tritiyatma; Darwis, Darsef (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This research is aiming to discover effect of the application of Team Assisted Individualization type of cooperative learning model towards learning outcomes students of class X MIA in the subject of electrolyte and non-electrolyte solutions. The design research used in this research is posttest-only nonequivalent control group. This research is performed in Class X MIA, 27 Senior High School Jakarta in academic year of 2018/2019. Sampling technique used in this research is purposive sampling, thus Class X MIA 1 defined as experiment class and Class X MIA 2 defined as control class. The learning model used in experiment class is Team Assisted Individualization learning model, while in the control class is using Active Learning. The results show that there’s a difference in student learning outcomes in experimental class and control class (tcount = 1,995; ttable = 1,668, tcount > ttable). It can be concluded that learning activities using Team Assisted Individualization learning models have a positive influence on student learning outcomes on the subject of electrolyte and non-electrolyte solutions. Keywords:Team Assisted Individualization Learning Model, StudentLearning Outcomes, Electrolyte andNon-electrolyte Solutions